Government of Assam Draft Eleventh Five Year Plan (2007-12) and Annual Plan (2007-08) Volume-I - Planning Commission (Planning Commission, 2007)
Assam, the gateway to the North East India, today is a State with a mission to accomplish accelerated development by overcoming both natural and man made growth barriers. Assam has been eternally blessed with a bountiful nature. The blue mountains with a wide array of fauna and flora; the mighty Brahmaputra and its tributaries and the Barak in south, providing abundant water resources; the dense forests covering wide range of medicinal plants; the oil and natural gas; the fertile valleys and hill slopes nourishing tea gardens, horticultural crops and vital food grains provide immense possibilities for economic development.
An Overview Summarised Eleventh Five Year Plan (2007-12) and Annual Plan (2007-08)